2011
DOI: 10.3892/etm.2011.274
|View full text |Cite
|
Sign up to set email alerts
|

Dentigerous cysts associated with impacted supernumerary teeth in the anterior maxilla

Abstract: Abstract. Dentigerous cysts are thought to be caused by a developmental abnormality derived from the reduced enamel epithelium of the tooth forming organ. Most typical dentigerous cysts are those associated with the third molar teeth of the mandible, but rarely involve impacted supernumerary teeth in the anterior maxilla. Swelling and/or pain may be the major complaints of the patients. Herein, we review the literature spanning the past 22 years concerning dentigerous cysts associated with supernumerary teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
16
0
3
Order By: Relevance
“…Dentigerous cysts is the second most frequent cystic lesion of the jaws, which usually encloses the crown of an unerupted tooth. The majority of the ST are inverted and often lead to complications, such as impaction of the permanent successor teeth, displacement of teeth, diastema, crowding, and the development of DC, which can resorb the roots of the adjacent permanent teeth …”
Section: Discussionmentioning
confidence: 99%
“…Dentigerous cysts is the second most frequent cystic lesion of the jaws, which usually encloses the crown of an unerupted tooth. The majority of the ST are inverted and often lead to complications, such as impaction of the permanent successor teeth, displacement of teeth, diastema, crowding, and the development of DC, which can resorb the roots of the adjacent permanent teeth …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hurlen and Humerfelt found a correlation of 7% and Asaumi et al stated that dentigerous cysts associated to supernumerary teeth account for 11% of the cases. A study by Lin et al showed that the connection between dentigerous cysts and supernumerary teeth was of 13% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Stafne was the first to describe dentigerous cysts associated with supernumerary teeth, registering an incidence of 5.5% in 200 dentigerous cysts 9 . The etiology of supernumerary teeth is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Kebanyakan kista dentigerous adalah yang berhubungan dengan gigi molar ketiga mandibula, diikuti oleh molar ketiga rahang atas, kaninus rahang atas dan premolar dari kedua tulang rahang atas dan tulang mandibular. 3 Sembilan puluh lima persen dari kista dentigerous berhubungan dengan gigi permanen sedangkan hanya 5% dengan gigi supernumerary. 4 Kista dentigerous dari sudut pandang klinis umumnya asimtomatik, tumbuh lambat, biasanya berhubungan dengan mahkota gigi impaksi dan gigi yang tidak erupsi.…”
Section: Pendahuluanunclassified